Climate change between the mid and late Holocene in northern high latitudes – Part 1: Survey of temperature and precipitation proxy data - J. Nilsson; H. Körnich; K. Holmgren; A. Moberg; Q. Zhang; H. S. Sundqvist; G. Brattström (Climate of the Past, 2010)
We undertake a study in two parts, where the overall aim is to quantitatively compare results from climate proxy data with results from several climate model simulations from the Paleoclimate Modelling Intercomparison Project for the mid-Holocene period and the pre-industrial, conditions for the pan-arctic region, north of 60° N. In this first paper, we survey the available published local temperature and precipitation proxy records. We also discuss and quantifiy some uncertainties in the estimated difference in climate between the two periods as recorded in the available data. The spatial distribution of available published local proxies has a marked geographical bias towards land areas surrounding the North Atlantic sector, especially Fennoscandia. The majority of the reconstructions are terrestrial, and there is a large over-representation towards summer temperature records. The available reconstructions indicate that the northern high latitudes were warmer in both summer, winter and the in annual mean temperature at the mid-Holocene (6000 BP ± 500 yrs) compared to the pre-industrial period (1500 AD ± 500 yrs). For usage in the model-data comparisons (in Part 1), we estimate the calibration uncertainty and also the internal variability in the proxy records, to derive a combined minimum uncertainty in the reconstructed temperature change between the two periods. Often, the calibration uncertainty alone, at a certain site, exceeds the actual reconstructed climate change at the site level. In high-density regions, however, neighbouring records can be merged into a composite record to increase the signal-to-noise ratio. The challenge of producing reliable inferred climate reconstructions for the Holocene cannot be underestimated, considering the fact that the estimated temperature and precipitation fluctuations during this period are in magnitude similar to, or lower than, the uncertainties the reconstructions. We advocate a more widespread practice of archiving proxy records as most of the potentially available ...